Fluid flow for chemical engineers. - Holland, F. A. (Edward Arnold, 1995)
In preparing the second edition of this book, the authors have been concerned to maintain or expand those aspects of the subject that are specific to chemical and process engineering. Thus, the chapter on gas-liquid two-phase flow has been extended to cover flow in the bubble regime as well as to provide an introduction to the homogeneous model and separated flow model for the other flow regimes. The chapter on non-Newtonian flow has also been extended to provide a greater emphasis on the Rabinowitsch-Mooney equation and its modification to deal with cases of apparent wall slip often encountered in the flow of suspensions. An elementary discussion of viscoelasticity has also been given.
Previous edition: 1973.
Includes index.
Keywords: Fluid dynamics -- Mathematics.; Chemical engineering.; elektronické knihy; electronic books